Techniques for Formation of Nagari Rules in Nagari Tuo Pariangan - Roni Efendi; Hebby Rahmatul Utamy; Afdi Bima (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
This article was the result of community service in Nagari Tuo Pariangan, Pariangan District, Tanah DatarRegency related to technical assistance in the drafting of the Nagari regulations. The Nagari Regulations are the statutedrafted by the village level legislature (BPRN/BAMUS) and Wali Nagari. Therefore, Nagari Regulations usually haveto be made in accordance with the provisions of laws and regulations. In order to be able to create good NagariRegulation, those who create nagari regulations must have to a holistic and comprehensive understanding of theprocedures for designing nagari regulations since planning untill clarification. The difference from other articles waswrited of this article endowed with a method of devotion participatory action research (PAR) and a shift in legislativefunction at the Nagari level to go to a traditional village.